(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, the speech expression of national-cultural features of idioms in the German language and their classification in dictionaries are briefly studied and explained with the help of examples. When establishing a phraseological alternative, special attention should be paid to the fact that the component expressing the main meaning of the phrase discovers a different meaning in different phrases. It is known that a number of somatic words are not used in the same sense in the formation of similar and dissimilar phrases in different languages, but are involved in different subtleties of meaning. In particular, it is often observed that such meaning shifts in the meaning and content of units expressing an abstract meaning. Even in the forms related to the expression of feelings and various emotional states, we observe that their content differs from each other with very fine edges. It is revealed that this is explained by the fact that language is a very complex means of communication, and its perception is very ancient and very fast.